Impacts of carrier trapping and ion migration on charge transport of perovskite solar cells with TiOx electron transport layer. Issue 47 (27th July 2020) - Li, Ling; Jia, Pengcheng; Bi, Wentao; Tang, Yang; Song, Bo; Qin, Liang; Lou, Zhidong; Hu, Yufeng; Teng, Feng; Hou, Yanbing
Abstract : The ion migration in perovskite materials has been extensively studied by researchers, but the charge dynamic distribution caused by ion migration and carrier trapping is partly unclear. Abstract : The ion migration in perovskite materials has been extensively studied by researchers, but the charge dynamic distribution caused by ion migration and carrier trapping is partly unclear. To investigate the impacts of ion migration and defect induced carrier trapping on the carrier transport and the carrier collection, we measured the evolution of the photocurrent response in microseconds, milliseconds and seconds for the perovskite solar cells pretreated at different biases. Our results reveal that the photocurrent of the solar cells pretreated at negative bias decreases with time and achieves its minimum at several milliseconds, then rises and achieves its maximum at tens of seconds. For the device pretreated at positive bias beyond built-in potential, the time to reach maximum photocurrent is much shorter than that of the solar cell pretreated at negative bias. The transient photocurrent responses to the sequence of single-light-pulses also show that there is obvious carrier trapping in a positive bias treated device, which indicates that defect induced carrier trapping is the critical factor for the perovskite solar cells with an n-TiO x electron transport layer. In order to improve the performance of the perovskite solar cells with nano-TiO x ETL, it is very necessary to significantly reduce defects. Our results also demonstrate that cation accumulation at the interface between the perovskite active layer and ETL can enhance the device performance to a certain extent.